2015
DOI: 10.1038/bmt.2015.308
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in hematopoietic stem cell transplant recipients

Abstract: Venous thromboembolism (VTE) is an increasingly recognized problem in the post-hematopoietic stem cell transplantation (HSCT) setting, with a lack of high-quality evidence-based data to recommend best practices. Few patients with hematologic malignancies and even fewer post-HSCT patients were included in randomized trials of VTE prophylaxis and treatment. Prior VTE, GVHD, infections and indwelling venous catheters are risk factors for thrombosis. The increasing use of post-transplant maintenance therapy with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 79 publications
1
27
1
Order By: Relevance
“…4 We found that double lumen catheters in the internal jugular vein were most commonly associated with thrombosis then single lumen or subclavian vein catheters, suggesting more caution is needed in some CVC approaches. Previous VTE is a well-recognized risk factor for subsequent VTE 8, 27 and we show this holds true for CRT as well. While we identified number of risk factors for post-AHCT VTE, we also acknowledge the retrospective nature of this study, incomplete list of potential risk factors analyzed and inherent bias of case-control analysis.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…4 We found that double lumen catheters in the internal jugular vein were most commonly associated with thrombosis then single lumen or subclavian vein catheters, suggesting more caution is needed in some CVC approaches. Previous VTE is a well-recognized risk factor for subsequent VTE 8, 27 and we show this holds true for CRT as well. While we identified number of risk factors for post-AHCT VTE, we also acknowledge the retrospective nature of this study, incomplete list of potential risk factors analyzed and inherent bias of case-control analysis.…”
Section: Discussionsupporting
confidence: 67%
“…The risk of thrombosis in multiple myeloma is low despite the use of lenalidomide after AHCT which may have added thrombotic risk. 8 The need for prophylactic anticoagulation therapy has been based on medical history and most patients receive aspirin or LMWH prophylaxis. 8 We showed that the majority of CRT events occurred at median 4 weeks post-transplant period which is consistent with Gerber et al report of thromboembolic events occurring at median interval of 35 days from either autologous or allogeneic transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations